The Role of the Guidance Studio (SB) as an Effort to Fulfill the Educational Rights of Indonesian Migrant Workers in Kuala Lumpur - Ayu Hakikatul Maula; Poppy Rachman; Babul Bahrudin; Fika Anajana; Wahyu Lestari (MASI Mandiri Edukasi, 2026)
Access to proper education is still a structural problem for Indonesian migrant children in Kuala Lumpur, Malaysia. The absence of immigration documents, administrative barriers, and limited family economic conditions has caused most migrant children to be unable to access formal education equally. This study aims to analyze the role of Guidance Studio as a community-based non-formal education program to ensure educational rights for Indonesian migrant children. This study uses a cumulative case study approach. Data was collected through in-depth interviews, participatory observations, and documentation during the author’s direct involvement as a volunteer teacher at the Guidance Studio. The results of the study show that the Guidance Studio plays a significant role in providing access to alternative education through flexible, context-based learning, strengthening basic literacy, and shaping the character and national identity of migrant children. Despite legal and resource limitations, the Guidance Studio remains committed to becoming a safe and inclusive space that ensures the fulfillment of children’s educational rights. These findings affirm the importance of community-based alternative education as a strategy in reducing inequality in access to education for marginalized groups of migrant children.